A One-Step, Monolayer Culture and Chemical-Based Approach to Generate Insulin-Producing Cells From Human Adipose-Derived Stem Cells to Mitigate Hyperglycemia in STZ-Induced Diabetic Rats. (August 2022) - Liang, Ruei-Yue; Zhang, Kai-Ling; Chuang, Ming-Hsi; Lin, Feng-Huei; Chen, Tzu-Chien; Lin, Jhih-Ni; Liang, Ya-Jyun; Li, Yi-An; Chen, Chun-Hung; Wong, Peggy Leh Jiunn; Lin, Shinn-Zong; Lin, Po-Cheng
The global population of individuals afflicted with diabetes mellitus has been increasing year by year, and this disease poses a serious threat to human health as well as the economies worldwide. Pancreatic or islet transplantations provide one of the most effective and long-term therapies available to treat diabetes, but the scarcity and quality of pancreatic islets limit their use in treatments. Here, we report the development of a one-step, monolayer culture, and chemical-based protocol that efficiently mediates the differentiation of human adipose-derived stem cells (hADSCs) into insulin-producing cells (IPCs). Our data indicate that hADSCs in monolayer culture that are allowed to differentiate into IPCs are superior to those in suspension cultures with respect to insulin secretion capacity (213-fold increase), cell viability (93.5 ± 3.27% vs. 41.67 ± 13.17%), and response to glucose stimulation. Moreover, the expression of genes associated with pancreatic lineage specification, such as PDX1, ISL1, and INS (encoding insulin), were expressed at significantly higher levels during our differentiation protocol (6-fold for PDX1 and ISL1, 11.5-fold for INS ). Importantly, in vivo studies demonstrated that transplantation with IPCs significantly mitigated hyperglycemia in streptozotocin-induced diabetic rats. Our results indicate that this one-step, rapid protocol increases the efficiency of IPC generation and that the chemical-based approach for IPC induction may reduce safety concerns associated with the use of IPCs for clinical applications, thereby providing a safe and effective cell-based treatment for diabetes.